Great adaptations : screenwriting and global storytelling - Krasilovsky, Alexis (Routledge, 2018)
"A vast majority of Academy Award-winning Best Pictures, television movies of the week, and mini-series are adaptations, watched by millions of people globally. Great Adaptations: Screenwriting and Global Storytelling examines the technical methods of adapting novels, short stories, plays, life stories, magazine articles, blogs, comic books, graphic novels and videogames from one medium to another, focusing on the screenplay. Written in a clear and succinct style, perfect for intermediate and advanced screenwriting students, Great Adaptations explores topics essential to fully appreciating the creative, historical and sociological aspects of the adaptation process. It also provides up-to-date, practical advice on the legalities of acquiring rights and optioning and selling adaptations, and is inclusive of a diverse variety of perspectives that will inspire and challenge students and practitioners alike."--Provided by publisher.